Effectiveness of Nepal’s E-Government Service Delivery: A Case of Department of Passport (DoP) (United Journal of Interdisciplinary Studies, 2024)
The COVID-19 pandemic situation made governments and citizens take part in the use of technology to render services. The use of technology has revitalized and revolutionized public administration in many countries. All technology-driven services delivery also enhanced the trust of citizens towards the e-government systems. Also, the Government of Nepal (GoN) is moving towards the system of online service rather than service through physical presence because the pandemic situations forced to adopt online platforms for requesting public services. At the same time, the engagement on online activities increased during the pandemic for communication and other service-related activities. ‘Passport’ is an essential document issued by the government of residence required to travel other countries. In order to get a passport an applicant submits the filled-up form to the Department of Passport (DoP) with verified information through District Administration Office (DAO). In Nepal for a quick processing of the passport, the applicants can visit DoP and do the processing from there too. The information verification of the applicants is a sensitive and lengthy process in Nepal, and it is a paper-based. The DoP has an online pre-enrollment system that facilitates passport application processing. We assume that the introduction of technology improves service delivery. In this paper, the online pre-enrollment system of DoP is analyzed using E-Government Maturity Models (E-GovMM), and SWOT analysis. The views of the officials from DoP on the use of the system is collected through a purposive survey. Our findings from the study showed that the maturity level of the pre-enrollment system is in alignment with the maturity model, and the online pre-enrollment system implementation in the DoP has improved the traditional passport processing process. The pandemic situations also highlighted the need of online systems so that the social distancing could be practiced avoiding the spread of virus. Such pandemic situations can be more pressing and frequent in upcoming time. The maturity of the existing systems is necessary for which government should upgrade policy, human resources and technology. There has to be collaboration among various government agencies to provide single window online service delivery, which can be a sustainable solution to provide public service delivery in any disruptive situation. The government should embrace the concept of system thinking to develop whole of a government through collaborative effort in improving the public service delivery though E-Government implementation.